Distribution of and association between the larger grain borer Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) and the maize weevil Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) in maize stores - Vowotor, K.A.; Meikle, W.G.; Ayertey, J.N.; Markham, R.H. (Journal of Stored Products Research, 2005)
Interspecific interactions between the larger grain borer Prostephanus truncatus and the maize weevil Sitophilus zeamais were studied during two storage seasons in maize stores, in Bénin. Maize ears, randomly sampled from farmers' grain stores, were 'reared out', i.e., kept for 4 weeks under controlled conditions for F1 to emerge, and periodically sampled, in order to examine colonisation patterns of P. truncatus and S. zeamais. For both storage seasons, P. truncatus and S. zeamais populations were sparsely aggregated and not associated with each other. The degree and strength of association increased with each monthly sampling occasion with the Ochiai, Jaccard and Dice indices of association. By the fourth sampling occasion, P. truncatus was found on most ears and on some ears in very high numbers (>300 insects). Almost all ears with P. truncatus contained at least a few S. zeamais individuals, but many ears with S. zeamais contained no P. truncatus. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Association; Colonization; Interspecific competition; Maize; Prostephanus truncatus; Sitophilus zeamais; Spatial distribution